Association of consumption of sugar-sweetened beverages with cognitive function among the adolescents aged 12–16 years in US, NHANES III, 1988–1994 - Yan, Xiaofang; Xu, Yingxia; Huang, Jitian; Li, Yanmei; Li, Qian; Zheng, Juan; Chen, Qingsong; Yang, Wenhan (Frontiers in Nutrition, 2022)
Objective As a major source of added sugar, the consumption of sugar-sweetened beverages (SSBs) continues to increase worldwide. The adverse health effects associated with SSBs are also risk factors for cognitive development, but studies on the relationship between SSBs and adolescents' cognitive function are limited. We used data released by the National Health and Nutrition Examination Survey (NHANES) III (1988–1994) to explore the association between the consumption of SSBs and cognitive function among children and adolescents aged 12–16 years in the United States. Methods and procedures A nationally representative population sample included 1,809 adolescents aged 12–16 years who participated in the United States NHANES from 1988 to 1994 and provided samples for the dietary intake frequency questionnaire and measures of cognitive function. Binary logistic regression was used to estimate the association between the frequency of SSB consumption and scores on cognitive function tests. Results This study of 1,809 adolescents aged 12–16 years comprised 963 girls (weighted proportion, 48.17%) and 846 boys (weighted, 51.83%), with a weighted mean (SE) age of 13.99 (0.05) years. Compared with adolescents who intake SSBs 0–1 times per week, those who drank 4–7 times per week had better scores in arithmetic, reading, and digit span tests, with odds ratios (ORs) of 0.36 (95% CI = 0.16–0.82), 0.35 (95% CI = 0.18–0.70), and 0.19 (95% CI = 0.08–0.44), respectively. The ORs for abnormal block design scores increase with the frequency of SSB intake after being adjusted for potential confounders (P for trend 0.02). Stratified analyses showed that compared with normal or below BMI, among overweight or obese individuals, the frequency of SSB intake had significant ORs for abnormal digit span scores (OR = 4.76, 95% CI = 1.19–18.96 vs. 0.35, 95% CI = 0.10–1.25; P for interaction = 0.01). Conclusion The positive associations of SSBs at moderate level intake with better scores in arithmetic, reading, and digit span were observed, but no dose-response relationship was identified at the overall level. Additionally, with the increasing frequency of SSB consumption, the risk of anomalous block design scores increased among US adolescents. Further investigation is warranted to confirm the association and mechanism between SSBs and cognitive function among adolescents.